Analisis Permasalahan Kredit Macet Dalam Koperasi KSU Bona Mandiri Jaya - Ripho Delzy Perkasa; Eka Pratiwi; Amelia Husna; Anisa Putri (Departement of Mathematics Education, 2024)
This study aims to analyze the issue of non-performing loans (NPLs) in the KSU Bona Mandiri Jaya Cooperative, focusing on the contributing internal and external factors, as well as evaluating the consequences and management strategies. Non-performing loans are a critical issue that can threaten the liquidity, reputation, and operational sustainability of the cooperative. This study employs a descriptive qualitative approach to gain an in-depth understanding of the phenomenon. The research methodology involves data collection techniques such as in-depth interviews with cooperative managers, members experiencing non-performing loans, and financial experts, as well as direct observation and analysis of related documents. The collected data are analyzed through a process of reduction, presentation, and conclusion drawing to identify key themes. The results of the study indicate that internal factors contributing to non-performing loans include weak credit analysis, lack of supervision and monitoring, members' financial management incapability, and insufficient financial training and education. External factors encompass macroeconomic conditions, business competition, natural disasters, and government policies. Non-performing loans significantly impact the cooperative’s liquidity, member trust, operational costs, income, and risk of bankruptcy. The conclusion of this study is that managing non-performing loans in KSU Bona Mandiri Jaya requires a holistic and sustainable approach. Recommended strategies include improving the credit assessment system, enhancing supervision and monitoring, providing financial training to members, implementing more conservative credit policies, diversifying products and services, and collaborating with external financial institutions. Implementing these strategies is expected to reduce the risk of non-performing loans and enhance the cooperative's stability and operational sustainability.